A brief history of cocaine : from Inca monarchs to Cali cartels : 500 years of cocaine dealing - Karch, Steven B. (Boca Raton : CRC/Taylor & Francis, 2006)
"This book shows how the commercialization of cocaine was driven by cartels, pharmaceutical companies, and private enterprises across Europe, Asia, and the United States. Featuring new and reorganized chapters, A Brief History of Cocaine, Second Edition contains the latest data and statistics that correlate drug trafficking to terrorism and illustrate recent trends in worldwide production, consumption, cost competition, and international transport. This book offers a well-rounded historical perspective that helps to explain why one of today's most illegal industries continues to thrive despite costly anti-drug campaigns. This book is ideal for criminal justice practitioners, teachers, students, and anyone interested in this topic." --(Publishers Description).
The Inca and Spanish conquests -- "Joyfulle news" -- Botanists, naturalists, and pedestrians -- Celebrity endorsements -- A cholo at Huarai -- Genies and furies -- Death by misadventure -- A new disease emerges -- Coca Java -- A beautiful white powder -- The first cocaine cartels -- Risk business -- The "legitimate business of poisoning Hindoos" -- Harpies in the West End -- Japan's adventures in the cocaine trade -- Cocaine pandemic?
Includes bibliographical references (p. 175-180) and index.
Keywords: Cocaine -- History; Cocaine -- history; Drug and Narcotic Control -- history; Histoire; Cocain; Cocaine; Geschichte 1500-2004; History